Historis Kebijakan Aborsi di Indonesia: Dari Undang-Undang hingga Fatwa - Fathimah, Anis Nur; Mabrur, Hasim; Muna, Nailal (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2025)
Abortion remains a topic of ongoing debate among religious scholars. While it is often deemed strictly prohibited, exceptions are made for valid reasons. From a legal perspective, abortion has long been associated with criminal acts. Those who perform abortions are often seen as committing crimes against humanity and engaging in extraordinary criminal behavior. In response, the government issued Government Regulation (PP) No. 28 of 2024, which, under Article 116, permits abortion for victims of sexual violence, provided there are medical emergencies that pose a threat to the safety of the rape victim. This article examines the dynamics and evolution of abortion policies in Indonesia. It employs a normative juridical research method combined with a historical approach. Primary sources analyzed include Indonesian laws and religious fatwas from organizations such as Nahdlatul Ulama, Muhammadiyah, the Indonesian Ulema Council (MUI), and the Indonesian Women’s Ulama Congress (KUPI). The study utilizes content analysis within a gender theory framework. This normative juridical analysis reveals that religious fatwas and state laws mutually support each other. In the 1990s, fatwas from religious institutions and state laws regarding abortion primarily blamed those who underwent the procedure. However, in the 2000s, there was a slight relaxation, allowing abortion under certain conditions, but with restrictions on gestational age, typically between 120 and 140 days. From the 2010s to the present, there has been a shift toward recognizing women as complete legal subjects, considering psychological, emotional, and preventive aspects in cases of abortion for rape victims. Fatwas and legal policies regarding abortion have increasingly aligned with the concept of  maslahah  (benefit or welfare), focusing on the well-being of women as victims. This study provides readers with a historical reference to abortion policies across various institutions in Indonesia. Future researchers are recommended to conduct empirical studies on abortion policies.